Advances in malignant glioma drug discovery - Reardon, David A.; Perry, James R.; Brandes, Alba A.; Jalali, Rakesh; Wick, Wolfgang (Expert opinion on drug discovery, 2011)
Introduction: Outcome for patients with glioblastoma (GBM), the most common malignant primary brain tumor among adults, remains poor. However, two key treatment options have recently generated meaningful improvements in outcome for GBM patients. The addition of temozolomide (a methylating chemotherapeutic agent) to surgical resection and radiation therapy increases survival and is the first evidence that systemic chemotherapy can benefit GBM patients. Also, bevacizumab (a humanized mAb against VEGF) has significant antitumor activity among recurrent GBM patients. Additional areas of ongoing research are generating more therapeutic options that offer exciting potential to build on these results and further improve the outcome for malignant glioma patients. Areas covered: This review describes three foci of advanced clinical research aimed at improving the outcome of GBM patients: protracted temozolomide dosing, VEGF-inhibiting agents and integrin inhibitors. This review also discusses potential clinical trial strategies to evaluate irreversible EGFR inhibitors as well as therapeutics targeting PI3K and the hedgehog signaling pathway. Expert opinion: Several factors limit the efficacy of therapeutics targeting GBM. However, significant advances from basic science laboratories have recently generated important insights into the pathophysiology and molecular genetic abnormalities of these tumors. Efforts to translate these findings into innovative treatment strategies offer substantial promise to overcome therapeutic hurdles and treat individual patients more effectively. Improved understanding of malignant glioma biology and factors associated with treatment response will probably lead to improved therapeutic options and a better patient outcome.
Gesehen am 14.09.2022